The use of remote sensing for estimating evapotranspiration in the rice fields in Malaysia - Mohammed Hilmi, Hassan Saad; Mohd Soom, Mohd Amin; Mohamed Shariff, Abdul Rashid (2005)
Evapotranspiration estimes are essential in irrigation schemes, water balance equation and meteorology and climatology studies. Malaysia uses more than 75% of its fresh water withdrawal for rice irrigation, but with only about 45% efficiency due to losses from spillage, seepage, deep percolation and evapotranspiration. Different methods have been developed to estimate evapotranspiration from remote sensing data. A study on evapotranspiration for rice was conducted in the Tanjung Karang automatic meteorological station was installed inside the field to collect data required for calculations of the evapotransipration using the CROPWAT software. Non- weighing lysimeters (91 cm x 91 cm x 61 cm) with attached casella hook were installed to measure the crop evapotranspiration at five different locations within the 19000 ha irrigation scheme. NOAA satellite data was used as data input to correlate the remote sensing data with field evatranspiration data. The observed ET from the lysimeters ranged from 3.9 to 5.9 mm/day. while ET by calculation ranged from 3.1 to 5.4 mm/day. The corresponding ET values from satellite data 4.3 to 6.5 mm/day. Considering ET measured by lysimeter as the most accurate method, ET determined using satellite data overestimates those obtained by lysimeter by 11% and CROPWAT underestimates by 13%. Estimation of actual water use is an essential requirement for strategic water resource planning at national and regional levels.